2020
DOI: 10.1177/0269881120967870
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific sensitivity to methamphetamine-induced schizophrenia-relevant behaviours in neuregulin 1 type III overexpressing mice

Abstract: Background: Gene–environment interactions contribute to schizophrenia aetiology. Neuregulin 1 is a well-established genetic risk factor for schizophrenia, and elevated expression of type III neuregulin 1 mRNA in the dorsolateral prefrontal cortex is observed in patients with a core risk haplotype. A mouse model of type III Nrg1 overexpression ( Nrg1 III tg) possesses face and construct validity for schizophrenia; however, the sensitivity of these transgenic mice to environmental risk factors relevant to schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 78 publications
(109 reference statements)
0
10
0
Order By: Relevance
“…These miRNAs are known to play a crucial role in cell communication in the CNS and peripheral system [140]. These investigators also showed decreased hippocampal protein levels of ErbB4 and NRG1, that might serve as markers of METH-induced psychosis [141,142].…”
Section: Pre-clinical Studiesmentioning
confidence: 88%
“…These miRNAs are known to play a crucial role in cell communication in the CNS and peripheral system [140]. These investigators also showed decreased hippocampal protein levels of ErbB4 and NRG1, that might serve as markers of METH-induced psychosis [141,142].…”
Section: Pre-clinical Studiesmentioning
confidence: 88%
“…In addition, females exhibited enhanced drug-induced locomotor activity for a longer period of time of drug withdrawal than male rats ( Ramos et al, 2020 ). Similarly, female mice showed greater locomotor activity after an acute injection of METH (0.1 mg/kg, 1.0 mg/kg and 4.0 mg/kg) ( Chesworth et al, 2021 ; Cullity et al, 2021 ; Ohia-Nwoko et al, 2017 ). In contrast to observations made in rats and mice, prairie voles injected with 0.2 mg/kg METH showed greater locomotor activity in males in comparison to female voles ( Perry et al, 2019 ).…”
Section: Animal Models Of Methamphetamine Use Disordermentioning
confidence: 89%
“…NRG1 is not only an EGF-like protein implicated in neural development and brain activity homeostasis [35] but also an important factor for memory formation and an indicator of Meth dependence [36], which regulates nerve cell differentiation, neuron migration, neurotransmission, neurite outgrowth, and synaptic activity and protects neurons under various pathological conditions [37]. Furthermore, recent evidence also suggested that NRG1 is an appropriate candidate gene for Meth-induced psychosis and overexpression of NRG1 type III modulated the behavioral tests induced by Meth [38,39]. In particular, neuregulins (NRGs) are cell-cell signaling proteins that act as ligands for receptor tyrosine kinases of the ErbB family.…”
Section: Discussionmentioning
confidence: 99%